A pilot study of same-day MRI-only simulation and treatment with MR-guided adaptive palliative radiotherapy (MAP-RT). (March 2023) - Schiff, Joshua P.; Maraghechi, Borna; Chin, Re-I.; Price, Alex; Laugeman, Eric; Rudra, Souman; Hatscher, Casey; Spraker, Matthew B.; Badiyan, Shahed N.; Henke, Lauren E.; Green, Olga; Kim, Hyun
Highlights: A pilot study of MRI-only simulation and treatment with palliative radiation. Simulation and first fraction were performed on the same day. Electron densities were derived using bulk density override method. 99% of fractions were completed at first on-table attempt. No grades 3 through 5 toxicities were recorded. Abstract: We conducted a prospective pilot study evaluating the feasibility of same day MRI-only simulation and treatment with MRI-guided adaptive palliative radiotherapy (MAP-RT) for urgent palliative indications (NCT#03824366). All (16/16) patients were able to complete 99% of their first on-table attempted fractions, and no grades 3–5 toxicities occurred.